Rapid Three-Dimensional Reconstruction of Underwater Defective Pile Based on Two-Dimensional Images Obtained Using Mechanically Scanned Imaging Sonar. (28th March 2023) - Shen, Sheng; Zeng, Yamian; Lai, Changqin; Jiang, Shaofei; Wu, Shaofen; Ma, Shenglan
Abstract : Three-dimensional (3-D) reconstruction based on sonar imaging is an intuitive and comprehensible form for describing an underwater defective pile. Most existing 3-D reconstruction methods are inefficient as they require the extraction of numerous feature points from many sonar images. A rapid 3-D reconstruction method for underwater defective piles based on two-dimensional (2-D) images obtained using mechanically scanned imaging sonar (MSIS) is proposed herein. First, the correspondences between the geometric features of MSIS images and actual defects are established based on the mapping relationship between actual object and MSIS image. Subsequently, no more than three feature points are extracted from 2-D MSIS images to recognize the contour segments. The contour segments are assembled into the entire cross section and then into the entire defective pile. The applicability of the proposed method is verified via a 3-D reconstruction for a scaled-down pile with multiple defect distributions.